2018
DOI: 10.1093/hropen/hoy004
|View full text |Cite
|
Sign up to set email alerts
|

ESHRE guideline: recurrent pregnancy loss

Abstract: STUDY QUESTION What is the recommended management of women with recurrent pregnancy loss (RPL) based on the best available evidence in the literature? SUMMARY ANSWER The guideline development group formulated 77 recommendations answering 18 key questions on investigations and treatments for RPL, and on how care should be organized. WHAT IS KNOWN ALREADY A pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
499
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(562 citation statements)
references
References 139 publications
1
499
0
16
Order By: Relevance
“…Recurrent pregnancy loss (RPL) can be identified based on an obstetrical history which includes the loss of two or more pregnancies and is known to affect about 1%‐2% of women . However, some aspects of the definition of RPL such as the condition of being “consecutive” and the requisite number of miscarriages have been disputed (Table ) . Here, we adopted the definition from The European Society of Human Reproduction and Embryology (ESHRE 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent pregnancy loss (RPL) can be identified based on an obstetrical history which includes the loss of two or more pregnancies and is known to affect about 1%‐2% of women . However, some aspects of the definition of RPL such as the condition of being “consecutive” and the requisite number of miscarriages have been disputed (Table ) . Here, we adopted the definition from The European Society of Human Reproduction and Embryology (ESHRE 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to ESHRE guideline for RPL testing for hereditary thrombophilia is not suggested unless the women have other risk factors, such as family history of hereditary thrombophilia or previous venous thromboembolism (VTE) [16]. However, according to a research, conducted among 154 Bulgarian women with single embryonic loss and 100 healthy controls, it was concluded that F V Leiden had an impact on adverse pregnancy outcomes, especially in the second and third trimester [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent miscarriage (RM), also known as recurrent pregnancy loss, is defined as experiencing at least two or three consecutive fetal deaths or spontaneous abortions before the 24th gestational week . Although RM has complex causes, including chromosome abnormalities, anatomical defects, acquired infection, antiphospholipid syndrome, and endocrine disease, the cause of RM remains unexplained in almost half of patients .…”
Section: The Role Of Cxcl16 In Pathological Pregnancymentioning
confidence: 99%